ANALISIS PENGARUH PDRB, PENGANGGURAN, PENDIDIKAN, DAN KESEHATAN TERHADAP KEMISKINAN DI JAWA TENGAH TAHUN 2004-2009 - Anggit Yoga Permana; Fitrie Arianti (Universitas Diponegoro, 2012)
ABSTRACT The high level of proverty in Central Java showed the process of economic development that have not been able to improve the welfare of society equally. Therefore, required the analysis of the factors that influence poverty in an attempt to overcome the poverty problem. The purpose of this study was to analyze the factors affecting poverty in 35 districts/cities in Central Java during the period 2004-2008. This study used secondary data analysis tool data panel, consisting of time series data over the period 2004-2009 and cross section 35 districts/cities in Central Java.One of the approachesused to estimate the panel data regression model is to use a fixed effects model, by including dummy variables in the equation, also called Least Square Dummy Variable (LSDV). The dummy variable used in this model because of differences in the characteristics and resource of each region. Results showed that the GDP growth rate variable, education, health has a negative and significant impact on poverty. Meanwhile, unemployment rate variable has a positive and significant effect on poverty.